Phytochemical Screening and Physical Evaluation of Liquid Soap Preparation with 96% Ethanol Extract of Butterfly Flower (Clitoria ternatea L.) - Ramdhini, Rizki Nisfi; Dewi, Sindi Sartika (Indonesian Journal of Advanced Research, 2024)
Telang is a type of plant that is often found in Indonesia. Butterfly pea plants, especially flowers, are widely used as natural dyes and herbal medicines because they have secondary metabolites such as phenolics, flavonoids and anthocyanins which have antibacterial potential. Based on its potential, it is necessary to innovate in making liquid soap cosmetic preparations using butterfly pea flower extract as an active ingredient that has antibacterial properties. The type of research is experimental laboratory including phytochemical screening of butterfly pea flower extract and formulation of liquid soap preparations with extract variations of 5%, 10% and 15%. The results of the research show that butterfly pea flower extract contains flavonoids, saponins, tannins, steroids, terpenoids and alkaloids. The results of the physical evaluation showed that the orgonoleptic test results, pH, spreadability, homogeneity and foam height met the requirements for good liquid soap.